2017
DOI: 10.1042/bsr20171157
|View full text |Cite
|
Sign up to set email alerts
|

Roles of miRNAs and long noncoding RNAs in the progression of diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is the leading cause of blindness in working-age adults across the world. The pathogenesis of DR is multifactorial and the molecular mechanisms are still not fully understood. Accumulating evidence has demonstrated that noncoding RNAs (ncRNAs) may be aberrantly expressed and may play vital roles in the development of DR. Amongst ncRNAs, miRNAs and long ncRNAs (lncRNAs) are known for their regulatory functions. Here, we summarize the functions and mechanisms of known aberrantly express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 135 publications
(152 reference statements)
2
97
1
Order By: Relevance
“…As previously reported, lncRNAs could competitively bind common miRNAs as ceRNAs [25,37,38] and regulate miR-223-3p expression by lncRNA-MEG3, which has been observed in other diseases [30].…”
Section: Lncrna-meg3 Functions As the Cerna Of Mir-223-3p In Drsupporting
confidence: 57%
See 1 more Smart Citation
“…As previously reported, lncRNAs could competitively bind common miRNAs as ceRNAs [25,37,38] and regulate miR-223-3p expression by lncRNA-MEG3, which has been observed in other diseases [30].…”
Section: Lncrna-meg3 Functions As the Cerna Of Mir-223-3p In Drsupporting
confidence: 57%
“…Still, the regulatory mechanisms involving TTR in DR are not entirely clear.Long non-coding RNAs (lncRNAs) regulate targeted mRNA expression via the microRNA (miRNA) response element known as competing endogenous RNA (ceRNA) [18,19]. LncRNAs are known to play vital roles in ocular disease [20], including glaucoma [21,22], retinoblastoma [23,24], and DR [25,26]. Recently, the study of lncRNAs in DR has become a hot point.…”
mentioning
confidence: 99%
“…The function of MRPL19 is unclear but other MRP genes including MRPL9 and MRPL23 are associated with retinitis pigmentosa (Kenmochi et al, 2001). Increasing evidence suggests a potential role of noncoding RNAs in regulating retinal inflammation during DR development (Gong & Su, 2017).…”
Section: Genetic Association With Retinopathiesmentioning
confidence: 99%
“…In this context, several studies have reported abnormal expression of microRNAs (miRNAs/miRs) in retinal cells under hyperglycemic conditions and in murine models of DR . MiRNAs are small endogenous non‐coding RNAs that in general silence gene expression at the posttranscriptional level by pairing to specific sequences in the 3’‐untranslated region of their target mRNAs, thereby repressing protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Epigenetic mechanisms, such as DNA methylation, histone post-translational modifications in chromatin and non-coding RNAs, mediate the interplay between genetic and environmental risk factors. Persistence of epigenetic changes might contribute to the metabolic memory phenomenon and to the oxidative stress, inflammation and extracellular matrix accumulation, 5,6 all of which lead to the development of DR. 5 In this context, several studies have reported abnormal expression of microRNAs (miRNAs/miRs) in retinal cells under hyperglycemic conditions and in murine models of DR. [7][8][9] MiRNAs are small endogenous non-coding RNAs that in general silence gene expression at the posttranscriptional level by pairing to specific sequences in the 3'-untranslated region of their target mRNAs, thereby repressing protein synthesis. MiRNAs regulate cell development and function by modulating the acquisition and maintenance of beta-cell identity, 10 cell growth, proliferation, differentiation, apoptosis and metabolism.…”
Section: Introductionmentioning
confidence: 99%